Agriculture, health, and nutrition: Towards conceptualizing the linkages - Hoddinott, John F. (International Food Policy Research Institute, 2011)
Strengthening the policy and programmatic links between agriculture and health and nutrition requires a means of seeing how their myriad links fit together. This brief sketches a framework that elucidates the channels through which agriculture affects health and nutrition and vice versa. While this framework can be applied at the global or national level, here it is focused on households and individuals, given that improving individual welfare is the ultimate goal of public policy.